2022
DOI: 10.1002/cptc.202200073
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Room‐Temperature Phosphorescence in Arylselanyl BODIPY‐Doped Materials

Abstract: Near‐infrared (NIR) luminescent materials have received considerable attention owing to their intriguing applications in fields such as high‐resolution biological imaging and information technology. In this context, room‐temperature phosphorescence (RTP) materials with emission bands in the NIR region are rare. Metal‐free arylselanyl‐BODIPY triplet photosensitizers were doped into a benzophenone (BP) matrix. When excited at 350 nm, RTP emission was observed in the NIR region with λem values of 750–816 nm, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Consequently, the excited-state mechanism through which the S 1 and T 1 of the guest are populated implies preferential photoexcitation of the BPO followed by quantitative ISC to its high-energy triplet, leading to the observation of longer-lived and superimposed fluorescence and phosphorescence of the isomers. Indeed, the triplet state of the BPO lies well above both the singlet and the triplet excited states of the phenothiazine derivatives (Table S11 and Figures S28 and S29); Förster resonance energy transfer between S 1 states as well as triplet–triplet energy transfer between host and guest may take place . On the other hand, TPP acts as a host providing a rigid and oxygen-poor environment where the phosphorescence of the guest is significant, with the guest S 1 state being the only excited state populated upon light absorption.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Consequently, the excited-state mechanism through which the S 1 and T 1 of the guest are populated implies preferential photoexcitation of the BPO followed by quantitative ISC to its high-energy triplet, leading to the observation of longer-lived and superimposed fluorescence and phosphorescence of the isomers. Indeed, the triplet state of the BPO lies well above both the singlet and the triplet excited states of the phenothiazine derivatives (Table S11 and Figures S28 and S29); Förster resonance energy transfer between S 1 states as well as triplet–triplet energy transfer between host and guest may take place . On the other hand, TPP acts as a host providing a rigid and oxygen-poor environment where the phosphorescence of the guest is significant, with the guest S 1 state being the only excited state populated upon light absorption.…”
Section: Resultsmentioning
confidence: 98%
“…Indeed, the triplet state of the BPO lies well above both the singlet and the triplet excited states of the phenothiazine derivatives ( Table S11 and Figures S28 and S29 ); Förster resonance energy transfer between S 1 states as well as triplet–triplet energy transfer between host and guest may take place. 61 On the other hand, TPP acts as a host providing a rigid and oxygen-poor environment where the phosphorescence of the guest is significant, with the guest S 1 state being the only excited state populated upon light absorption. Figure 5 (at the bottom right) shows the recorded decay kinetics for the phosphorescence emission of the host–guest matrices.…”
Section: Resultsmentioning
confidence: 99%
“…Limited by the energy gap law, phosphorescent materials emitting in the NIR-I spectral window are very rare. 254 Generally, the corresponding lifetimes are significantly shorter than those of room-temperature phosphorescence with the maximum bands in the visible window described above. Here, this part of Review will introduce several typical strategies to design and synthesize near-infrared phosphorescent materials as follows.…”
Section: Phosphorescence In the First Near-infrared Spectral Windowmentioning
confidence: 95%
“…Limited by the energy gap law, phosphorescent materials emitting in the NIR-I spectral window are very rare . Generally, the corresponding lifetimes are significantly shorter than those of room-temperature phosphorescence with the maximum bands in the visible window described above.…”
Section: Synthesis Strategies Of Room-temperature Phosphorescence In ...mentioning
confidence: 99%
“…As far as we know, there are limited reports on NIR RTP emission. Yuji et al developed host (benzophenone)–guest (arylselanyl-BODIPY) crystals, which emitted NIR RTP with the maximum emission at 750 nm in 0.48% quantum yield and a long lifetime of 18.5 ms. Yu and co-workers exhibited NIR RTP via a supramolecular macrocyclic confinement strategy with an emission wavelength of up to 800 nm in an aqueous solution with a lifetime from 21.3 μs to 0.364 ms. Zhang et al demonstrated that single crystals of succinimide-derived cyclic imides could emit NIR RTP (745 nm) with high efficiencies of up to 9.2% through clustering and halogen effects. Organic room temperature phosphorescence materials with long wavelengths (600/657–681/732 nm) and long lifetimes (102–324 ms) through the guest–host-doped strategy have been reported by Huang and co-workers .…”
Section: Introductionmentioning
confidence: 99%